2011
DOI: 10.1097/fjc.0b013e31821a50a8
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgolide B Reduces Inflammatory Protein Expression in Oxidized Low-density Lipoprotein-stimulated Human Vascular Endothelial Cells

Abstract: Ginkgolide B is a herbal constituent extracted from leaves of the ginkgo biloba tree. Previous studies have shown that ginkgolide B is a specific platelet activating factor (PAF) receptor antagonist, and it suppresses PAF-mediated platelet activation via competitive binding. In this study, the effect of ginkgolide B on nicotinamide adenine dinucleotide phosphate oxidase and other inflammatory proteins in ox-LDL (low-density lipoprotein)-stimulated human vascular endothelial cells was investigated. Another PAF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…In the next set of experiments, we have investigated whether the anti-inflammatory natural compounds α -Lipoic acid [2328] and Ginkgo biloba derivatives [29, 30] affected the release of cytokines/chemokines by pathological VEC. Indeed, although it has already been reported that both compounds, and in particular α -Lipoic acid, exhibit anti-inflammatory activities both in vitro and in vivo in the context of endothelial biology of different pathologies [2327], it remains to be established whether these compounds are active also on pathological VEC isolated from CVD patients.…”
Section: Resultsmentioning
confidence: 99%
“…In the next set of experiments, we have investigated whether the anti-inflammatory natural compounds α -Lipoic acid [2328] and Ginkgo biloba derivatives [29, 30] affected the release of cytokines/chemokines by pathological VEC. Indeed, although it has already been reported that both compounds, and in particular α -Lipoic acid, exhibit anti-inflammatory activities both in vitro and in vivo in the context of endothelial biology of different pathologies [2327], it remains to be established whether these compounds are active also on pathological VEC isolated from CVD patients.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies showed that ginkgolide B inhibited inflammatory protein expression induced by ox-LDL in human umbilical vein endothelial cells (HUVECs), such as intercellular adhesion molecule-1 (ICAM-1) and monocyte chemotactic protein-1 (MCP-1) expression, by inhibiting nuclear factor-kB (NF-kB) activation and reducing Nox4 expression in ox-LDL-treated endothelial cells [11], [12]. However, whether ginkgolide B influences LOX-1 expression in HUVECs has not yet been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been found that GB can reduce inflammatory protein expression in oxidized low-density lipoprotein-stimulated human vascular endothelial cells and lipopolysaccharidestimulated mouse peritoneal macrophages via blocking NF-B activation (Nie et al, 2004;Li et al, 2009;Zhang et al, 2011). In the central nervous system, after contusion spinal cord injury, treatment with GB led to significantly increased white matter tissue sparing as well as decreased mRNA levels for proinflammatory cytokines (Wang and Sun, 2000).…”
Section: Discussionmentioning
confidence: 99%